The impact of climate change on electricity demand in the city of Huancayo - Condori Clemente, Jennifer (2022)
This paper analyses how climate change affects electricity demand in the city of Huancayo, Peru, in order to find the relationship between electricity demand and temperature in degree Celsius in the last 20 years, using Spearman correlation, based on heating degree days (HDD), cooling degree days (CDD) and electricity demand data in Mw, the conversion of average temperatures to degree days showed that only heating degree days (HDD) were found, our statistical results show that there is a moderate inverse relationship, which means that in the last 20 years the increase in electricity demand was partially due to lower temperatures, since these cause higher heating needs and thus increased electricity demand. It is suggested that the research can be carried out in different parts of Peru, since the results may vary due to the diversity of climates and it is also of utmost importance to work carefully with the temperature data, to have accurate results. This gives us a notion that energy reserves should be prepared, and the use of renewable energies must be implemented with greater emphasis.